Upgrading Status of Right to Builds (HGB) Above The Right Management (HPL) Perumnas to Become Ownership Right (HM) (Case Study at Korpri Housing Bangetayu Wetan Semarang) - Dian Yunanti Yakob Udi; Titin Prialianti (Jurnal Akta, 2018)
In order to facilitate the middle to lower economic level people to have a decent housing, the government established Perumnas. Citizens wishing to improve their land title to HM (Ownership Right) on residential houses purchased from the Right to Use (HGB). This process must meet the prescribed requirements. The research method used was sociological juridical approach with analytical descriptive research specification, while the data analysis method used was descriptive qualitative. Based on the results of study in Korpri Housing Bangetayu Wetan Semarang and Land Office of Semarang City, it can be concluded that the procedure for submission of HGB to HM, the applicant has to visit the Land Office of Semarang City and complete some administrative requirements in the form of filling registration form, ID Card, IMB, HPL Holders Recommendation Perumnas, SPPT PBB of the current year, land ownership statement not more than 5 fields, and power of attorney if the application is authorized. Some obstacles in the application of the upgrade from SHGB on HPL Perumnas land become SHM are some people do not know or less understand about the procedure and requirement to upgrade their right, so that they give authorized to Notary/PPAT (Land Deed Officials), effort in IMB, the house is used as houseshop instead of residence. The way to solve it is by conducting further socialization to the community through BPN (National Land Agency) service, Notary/PPAT and physical inspection of residential houses for which the rights are requested.Keywords: Housing; Perumnas; Right to Manage; Ownership Right; Right to Builds.